Dynamics between Economic Integration and Informal Cross Border Trade and its Applicability in Cameroon and Equatorial Guinea - (:unkn) unknown (My University, 2024)
The present study highlights about dynamics between Economic Integration and Informal Cross Border Trade and Its Applicability in Cameroon and Equatorial Guinea. Collective self-reliance, inward-looking regionalism, and delinking from the dominant relationships that prevailed in the international economic system in the form of regional economic integration and cooperation was the solution identified by the Pan-African leaders as a potential strategy for restructuring the fragmented African region into a more coherent and viable economic space. However, the approaches, practices, and visions of these regional integration schemes are not contextualised into the African reality. Macroeconomic policies are such that Informal Cross Border Trade (ICBT) has become the veritable economic integration in Africa. This study interrogates the applicability and understanding of Economic Integration within the ECCAS Region while determining the influence Informal Cross Border Trade has had on economic integration in this sub-region. The study uses economic integration theories to analyse the implementation of Regional economic integration and its effectiveness. The study applies a qualitative research method with a cross-sectional design to study a multilevel issue involved in regional integration. It aimed to explain and predict phenomena based on empirical data obtained through interviews using closely structured and unstructured interview guides. The findings indicate that the non-implementation of the policies of regional integration especially the free movement of persons and goods, non-tariff barriers, and the lack of political will from some governments has been the major challenge for traders in the phase of informal cross-border trade. The study revealed that despite efforts to institutionalise regional integration in the ECCAS region, structural challenges remain a significant impediment to intra-regional trade. Informal cross-border traders consolidate wh
Keywords: African Research